CREDIT RISK DYNAMICS IN CZECH REPUBLIC - Sumna, Petra (European Scientific Journal, ESJ, 2013)
This paper discusses the credit risk management in banks in the Czech Republic and its dynamics in the pre-crisis period, in the crisis and after crisis. In this period of time there are monitored basic indicators related to credit risk, value adjustments for the risk, the number of loans in default and links of individual variables. This paper discusses the credit risk, and ways in which it operates in conjunction with the business cycle, as well as the development of credit risk in credit dynamics in the course of the business cycle. Damping of the fluctuations in the credit dynamics in the course of the economic cycle is devoted to, for example, Frait, Komárková (2008). Models of bank financing of Czech corporations and credit risk is discussed in a study Grešl, Jakubik (2008). The main objective of the paper is an analysis of the procyclicality of the three main banking entities in the Czech Republic. The sub-objective of this paper is assessment of the linearity of the relationship between the volume of granted loans and the number of adjustments to individual types of loans.